PANDAI MEMBACA Al-QUR’AN SEBAGAI PERSYARATAN NIKAH BAGI CALON PENGANTIN PERSPEKTIF HUKUM ISLAM (STUDI TERHADAP PERATURAN DAERAH KABUPATEN MANDAILING NATAL NOMOR 5 TAHUN 2003 DAN IMPLEMENTASINYA DI KANTOR URUSAN AGAMA KECAMATAN SINUNUKAN - Silfia Afriani; Ach. Faisol; Dzulfikar Rodafi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
The research aims to describe the viewpoint of Islamic law on regional regulation number 5 of 2003 which obliges the prospective bride and groom to be good at reading the qur’an, otherwise their marriage will be canceled/postponed. The research also aims to determine of these regional regulations in the Sinunukan religious affairs office. The research is a qualitative research with the type of case study research, the main instrument in this research is the researcher himself. Data collection techniques used in this study are library research, observation, interviews and documentation, after the data is obtained, the data is analyzed using data condensation, conclusions and data verification. The results of the research show that there’s a mismatch between the requirements given by the regional regulation and the conditions set by Islamic law, but if is seen from the point of view of maslahah mursalah then the regulations may be applied. The results of research also show this since the beginning this regulation was stipulated in the religious affairs office of Sinunukan sub-district, no data was found on the number of prospective brides who were not good at reading in the Al-Qur’an.ut can be concluded that the regulations are not implemented perfectly. Kata Kunci: Al-Qur’an, Pernikahan, Hukum Islam, Peraturan Daerah, Impleementasi.